Elucidating the functional role and therapeutic potential of La-related protein 1B (LARP1B) in cancer and its interplay with other LARP family members - Nawaz, A (2023)
RNA binding proteins (RBPs) are indispensable regulators of gene expression with a growing body of evidence demonstrating their role in cellular acquisition of the hallmarks of cancer. By regulating the expression of hallmark regulatory genes, RBPs mediate key cancer phenotypes including sustained cell proliferation, evasion from apoptosis and the regulation of cellular energetics. An exemplary group of RBPs known as the La-related proteins (LARPs) which include LARP1, LARP1B, La, LARP4, LARP4B, LARP6 and LARP7, are established regulators of mRNA translation and most are also known cancer effectors associated with cancer hallmarks. Whilst some LARPs such as LARP1 demonstrate pro-tumorigenic roles, others such as LARP7 exhibit anti-tumorigenic functions highlighting even intrafamilial diversity. To date, LARP1B has remained the “dark horse” of the family with little to no knowledge regarding the biological processes it regulates or participates in or its involvement in cancer. As such, this thesis provides a comprehensive analysis into the phenotypic and functional role of LARP1B in the context of cancer and to the best of our knowledge is the first study to do so. Our interrogation of the LARP1B protein interactome revealed several novel candidates implicated in diverse biological processes ranging from cytoplasmic translation to metabolic processes and the regulation of mitochondrial gene expression. Within this, a striking finding was the identification of many nuclear-localised proteins bound to LARP1B revealing previously unknown characteristics of nuclear-cytoplasmic shuttling, suggesting a diverse LARP1B-ribonucleoprotein (RNP) portfolio. Importantly, we observed an affinity for LARP1B expression in testicular tissue and testicular germ cell tumour (TGCT) cells in which LARP1B appeared to regulate intracellular reactive oxygen species (ROS) levels and mitochondrial function. Following LARP1B depletion, we observed a significant impact on cellular fitness and growth which we attributed to oxidative stress and mitochondria dysfunction-induced cytotoxicity and apoptosis. Given that testicular germ cells and surrounding tissue are highly sensitive to oxidative stress which can have severe adverse effects on sperm quality and function, these findings hint at an important role for LARP1B in the protection of testicular germ cells. Implications of this extend from male infertility to TGCT development which are often interlinked and are important considerations for the preservation of species.